Comparative study on the properties of starch-based bioplastics incorporated with palm oil and epoxidized palm oil. (9th March 2022) - Yang, Jianlei; Ching, Yern Chee; Julai J, Sabariah; Chuah, Cheng Hock; Nguyen, Dai Hai; Lin, Pai-Chen
This study aimed to modify the starch-based bioplastics with acceptable mechanical and water resistance properties using palm oil (PO) and epoxidized palm oil (EPO). The structural, thermal, mechanical and water resistance properties of the resulted bio-composites were evaluated. EPO had better compatibility within the starch matrix than PO. The bioplastics with PO and EPO exhibited different melting behaviors. Low concentrations of oils (<3 wt%) improved the tensile strength and elongation at break of the bioplastics remarkably, while higher concentrations of oils caused the decrease of tensile properties due to phase separation. Comparatively, EPO was more efficient at enhancing tensile properties than PO due to the presence of epoxy groups. Both oils reduced the water uptake and solubility of the bio-composites slightly. In conclusion, the addition of EPO was a more attractive way to enhance the properties of starch-based bioplastics.